Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine the average rate of change of the function [tex]\( f(z) = 1 - 3z^2 \)[/tex] between [tex]\( z = -2 \)[/tex] and [tex]\( z = 0 \)[/tex], we can follow these steps:
1. Calculate the function value at [tex]\( z = -2 \)[/tex]:
[tex]\[ f(-2) = 1 - 3(-2)^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ f(-2) = 1 - 3(4) \][/tex]
[tex]\[ f(-2) = 1 - 12 \][/tex]
[tex]\[ f(-2) = -11 \][/tex]
2. Calculate the function value at [tex]\( z = 0 \)[/tex]:
[tex]\[ f(0) = 1 - 3(0)^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ f(0) = 1 - 3(0) \][/tex]
[tex]\[ f(0) = 1 \][/tex]
3. Determine the change in the function values ([tex]\( \Delta f \)[/tex]):
[tex]\[ \Delta f = f(0) - f(-2) \][/tex]
Substituting the calculated values:
[tex]\[ \Delta f = 1 - (-11) \][/tex]
[tex]\[ \Delta f = 1 + 11 \][/tex]
[tex]\[ \Delta f = 12 \][/tex]
4. Determine the change in the input values ([tex]\( \Delta z \)[/tex]):
[tex]\[ \Delta z = 0 - (-2) \][/tex]
[tex]\[ \Delta z = 0 + 2 \][/tex]
[tex]\[ \Delta z = 2 \][/tex]
5. Calculate the average rate of change:
[tex]\[ \text{Average Rate of Change} = \frac{\Delta f}{\Delta z} \][/tex]
Substituting the values:
[tex]\[ \text{Average Rate of Change} = \frac{12}{2} \][/tex]
[tex]\[ \text{Average Rate of Change} = 6.0 \][/tex]
So,
- The function value at [tex]\( z = -2 \)[/tex] is [tex]\( -11 \)[/tex].
- The function value at [tex]\( z = 0 \)[/tex] is [tex]\( 1 \)[/tex].
- The average rate of change of the function [tex]\( f(z) = 1 - 3z^2 \)[/tex] between [tex]\( z = -2 \)[/tex] and [tex]\( z = 0 \)[/tex] is [tex]\( 6.0 \)[/tex].
1. Calculate the function value at [tex]\( z = -2 \)[/tex]:
[tex]\[ f(-2) = 1 - 3(-2)^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ f(-2) = 1 - 3(4) \][/tex]
[tex]\[ f(-2) = 1 - 12 \][/tex]
[tex]\[ f(-2) = -11 \][/tex]
2. Calculate the function value at [tex]\( z = 0 \)[/tex]:
[tex]\[ f(0) = 1 - 3(0)^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ f(0) = 1 - 3(0) \][/tex]
[tex]\[ f(0) = 1 \][/tex]
3. Determine the change in the function values ([tex]\( \Delta f \)[/tex]):
[tex]\[ \Delta f = f(0) - f(-2) \][/tex]
Substituting the calculated values:
[tex]\[ \Delta f = 1 - (-11) \][/tex]
[tex]\[ \Delta f = 1 + 11 \][/tex]
[tex]\[ \Delta f = 12 \][/tex]
4. Determine the change in the input values ([tex]\( \Delta z \)[/tex]):
[tex]\[ \Delta z = 0 - (-2) \][/tex]
[tex]\[ \Delta z = 0 + 2 \][/tex]
[tex]\[ \Delta z = 2 \][/tex]
5. Calculate the average rate of change:
[tex]\[ \text{Average Rate of Change} = \frac{\Delta f}{\Delta z} \][/tex]
Substituting the values:
[tex]\[ \text{Average Rate of Change} = \frac{12}{2} \][/tex]
[tex]\[ \text{Average Rate of Change} = 6.0 \][/tex]
So,
- The function value at [tex]\( z = -2 \)[/tex] is [tex]\( -11 \)[/tex].
- The function value at [tex]\( z = 0 \)[/tex] is [tex]\( 1 \)[/tex].
- The average rate of change of the function [tex]\( f(z) = 1 - 3z^2 \)[/tex] between [tex]\( z = -2 \)[/tex] and [tex]\( z = 0 \)[/tex] is [tex]\( 6.0 \)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.